Temperature-dependent regulation of bacterial cell division hydrolases by the coordinated action of a regulatory RNA and the ClpXP protease - Viktor H. Mebus; Larissa M. Busch; Morten Børre; Tobias K. Nielsen; Martin Saxtorph Bojer; Camilla Henriksen; Maria D. Barbuti; Danae M. Angeles; Kamilla Brejndal; Stephan Michalik; Manuela Gesell Salazar; Morten Kjos; et al. (The Cell Surface)
A defining feature of bacteria is the peptidoglycan cell wall which provides structural integrity and prevents osmotic lysis. While peptidoglycan hydrolases are required for daughter cell separation, dysregulated cell wall degradation may result in cell lysis. The mechanisms allowing bacteria to control these deadly enzymes in response to environmental changes remain incompletely understood. Here, we find that in Staphylococcus aureus, temperature-dependent regulation of such hydrolases occurs by the coordinated action of a CHAP domain-specific regulatory RNA and the ClpXP protease. Using a proteomics approach, we identify a hitherto uncharacterized ClpXP controlled autolysin, CxcA, with a catalytic CHAP domain and show that it contributes to separation of daughter cells. CxcA is positively controlled by a non-coding RNA, named Rbc1 (for RNA binding to CHAP domain) transcribed from the antisense strand of cxcA. Notably, Rbc1 is capable of base pairing with RNAs encoding the CHAP domains of numerous cell wall hydrolases and we show that Rbc1 works in trans to upregulate the cell division hydrolase Sle1. Specifically, Rbc1 functions as a thermosensor allowing for upregulation of CxcA and Sle1 at low temperature where daughter cell separation is impeded. Interestingly, the Rbc1-mediated up-regulation of CxcA and Sle1 does not involve mRNA stabilization or increased translation; instead, Rbc1 depletion increases ClpXP-mediated degradation. In conclusion, we identify a novel cell division hydrolase that is highly conserved in Staphylococci and show that it is co-regulated with enzymes containing the catalytic CHAP domain via transcriptional regulation, an RNA-RNA temperature sensory mechanism and the ClpXP protease.